DEVELOPMENT OF ALTERNATIVE LEARNING RESOURCES FORM OF INTERACTIVE SLIDE WITH APPROACH OF LEARNING STYLES ON DIVERSITY OF LIVING MATTER - HIMATUL MUFIDAH (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The objective this research are produces interactive slide with a viable approach to learning styles is used as an alternative learning resources, to describe the feasibility of interactive slide learning styles approach as an alternative learning resources, to describe the response of students to the interactive slides with style approach to learning, and to describe students behavior during trial of interactive slides with learning style approach. This type of research is performed with six development stages, among others, 1) analysis of student characteristics, 2) formulate learning objectives, 3) determine the types of learning resources and materials used, 4) organize an interactive slide diversity of living things, 5) study of the members, and 6) the trial limited. Alternative Learning Resources Form of Interactive Slide with Approach of Learning Styles on Diversity of Living Matter declared fit for use as an alternative learning resource by the percentage feasibility criteria in terms of content and format of learning resources as large as 92.08%, and get a very good response from students, as an alternative learning resource with big percentage of revenue 97.5%. Keyword: Development of learning resources, Interactive Slide, Style learning.